Threatened segetal flora species of the Łódź Heights - Warcholińska, Aurelia U. (Biodiversity: Research and Conservation, 2006)
The paper presents the results of floristic investigations of the threatened segetal plants of the Łódź Heights. In the course of the studies, 59 such species have been recorded. They constitute 18.2% of the segetal flora of this mesoregion and represent the following threat categories: CR (Critically Endangered) - 1 species, EN (Endangered) - 13 species, VU (Vulnerable) - 31 species, LC (Lower Risk) - 8 species, DD (Data Deficient) - 6 species.